2019
DOI: 10.1177/1724600818820679
|View full text |Cite
|
Sign up to set email alerts
|

Serum carcinoembryonic antigen to predict recurrence in the follow-up of patients with colorectal cancer

Abstract: Introduction: Serum carcinoembryonic (CEA) antigen is used as a diagnostic screening tool during follow-up in colorectal cancer patients. However, it remains unclear whether preoperative serum CEA is a reliable marker in the follow-up to predict recurrence. The aim of the study is to determine the value of elevated pre-and postoperative serum carcinoembryonic antigen levels (CEA > 5 µg/L) as an independent prognostic factor for locoregional and distant recurrence in patients who underwent curative surgery for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Results from clinical trials [54,55] suggests that compared to surgery alone, adjuvant chemotherapy improved the cure and decreased the risk of death. Recurrence rate for stage II is lower, compared to higher stages [56], but to date, no good marker has been found that may predict recurrences [57][58][59]. Although the present study could not provide data to supporting this hypothesis, but in our opinion, at the diagnosis of CRC or after primary surgery, when all staging data are available, calculating the PIT value could provide some guidance for future therapeutic decisions.…”
Section: Discussionmentioning
confidence: 72%
“…Results from clinical trials [54,55] suggests that compared to surgery alone, adjuvant chemotherapy improved the cure and decreased the risk of death. Recurrence rate for stage II is lower, compared to higher stages [56], but to date, no good marker has been found that may predict recurrences [57][58][59]. Although the present study could not provide data to supporting this hypothesis, but in our opinion, at the diagnosis of CRC or after primary surgery, when all staging data are available, calculating the PIT value could provide some guidance for future therapeutic decisions.…”
Section: Discussionmentioning
confidence: 72%
“…8 Approximately 70% of colorectal tumors consist largely of CEA-negative cell lines, and they are documented to have scarce or no CEA secretion, 9 which is consistent with previous findings that CEA-negative tumors constitute 49% to 75% of CRCs. [10][11][12][13] Therefore, we speculated that the recurrent disease that develops from primary tumors with negative CEA tends to sustain a low serum CEA level in surveillance tests and that the role of CEA in surveillance for patients with negative baseline CEA needs to be evaluated with a cohort study.…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the potential of the CEA apt -TDN-MOF for clinical uses, the detection of CEA in human serum was carried out by using CEA apt -TDN-MOF and confirmed by standardized ELISA. According to clinical studies, the level of CEA in serum is closely related to the occurrence of colon cancer [ 33 , 34 ]. Therefore, the serum samples from healthy individuals, patients with early colon cancer, and patients with advanced colon cancer were used.…”
Section: Resultsmentioning
confidence: 99%